Aid and fragile states - Anke Hoeffler; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Aid is still an important feature of the development landscape. Fragile states, in particular, have the greatest development needs but due to their poor governance they are the least likely countries to use aid effectively to meet their development challenges. In this paper, we explore which fragile states receive most aid flows, which donors are particularly active in fragile states, and which type of projects are the focus of these aid flows to fragile states. Evidence so far suggests that the high number of donors and the volatility of ODA generate problems for recipients who are least able to deal with the issues of donor coordination and budget planning under uncertainty. Furthermore, despite different needs, aid spending patterns to fragile countries are not very different from the average recipient country, although extremely fragile countries benefit from aid targeted at humanitarian and peacebuilding needs. We suggest that aid in fragile states could be best allocated to address the specific needs of these countries, especially countries in the 'fragile' category that may be at risk of falling into the 'extremely fragile' category. Using specific aid flows to prevent such shifts could be a useful strategy for donors engaged in those countries.
Keywords: 330; aid; development; fragility; conflict; post-conflict